A relação entre duas personagens femininas machadianas e a mulher contemporânea no contexto socioeducacional - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
In the socio-educational scope, promoting discussions related to reading and the literary text provides spaces for reflection on the constant changes in society. Machado’s female characters, Capitu and Sofia, in the works “Dom Casmurro” and “Quincas Borba”, are starting points for the elaboration of reflections on what we call being women – insofar as they are non-fictional – in contemporary times and in the world. context of education. We seek to analyze how the set of cultural production, in different texts, practices and patterns, expands and diversifies in order to answer the question: which elements of the literary narrative delineated, in two female characters from Machado, establish a relationship with the contemporary woman in the context socio-educational? We aim to understand the elements of literary narrative outlined in two works by Machado de Assis: “Dom Casmurro” and “Quincas Borba” and their relationship with the socio-educational context of contemporary women. To this end, we established the following specific research objectives: contextualize the historical time of the analyzed literary works, “Dom Casmurro” and “Quincas Borba” by Machado de Assis, in a socio-educational context; analyze the female characters, Capitu and Sofia, contextualizing them in the historical moment of Brazilian culture in the 19th century; and establish the relationship between two characters from Machado and the contemporary woman in the socio-educational context. To this end, methodologically, we followed an exploratory research, with a qualitative approach, with a bibliographical research and study of two literary works, in the proposition of a literary teaching. As a theoretical reference, we used authors from interdisciplinary fields (CHARTIER, 1990; SANTOS, K., 2015; COSTA, 2012; SCHWARZ, 1997; SAFFIOTI, 2015; BEAUVOIR, 2009; LOURO, 1997, 2000, 2004) to describe the context of women of the 19th century; for literary analysis in the nineteenth century, we base ourselves on D'incao (2011), Castello (2008), Eagleton (2003), Pound (2006), Passos (2003) and Candido (1968) to relate the female role between the 19th and 21st centuries. By examining the literary narratives of “Dom Casmurro” and “Quincas Borba” and the female characters of Capitu and Sofia in Machado's literature, we established the relationship with contemporary women in the socio-educational context. We reinforce that teaching literature is fundamental for the development of egalitarian movements and critical thinking about women. By analyzing these characters, we contextualize the Brazilian culture of the 19th century, showing restrictions on women's choices and society's pressure on their behavior. The course of the dissertation, based on education, literature and literature teaching, showed the need to continue the discussion about the role of women in contemporary society in different contexts.
The relationship between two female characters from Machado and the contemporary woman in the socio-educational context
Keywords: Narrativa literária - Capitu e Sofia de Machado de Assis - Mulher contemporânea; Capitu e Sofia de Machado de Assis - Mulher contemporânea - Contexto socioeducacional; Mulher contemporânea - Narrativa literária - Capitu e Sofia de Machado de Assis; LETRAS::LITERATURA BRASILEIRA; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::SOCIOLOGIA